Intermediate Co/Ni-base model superalloys — Thermophysical properties, creep and oxidation. (February 2016) - Zenk, Christopher H.; Neumeier, Steffen; Engl, Nicole M.; Fries, Suzana G.; Dolotko, Oleksandr; Weiser, Martin; Virtanen, Sannakaisa; Göken, Mathias
Abstract: The mechanical properties of γ ′-strengthened Co–Ni–Al–W–Cr model superalloys extending from pure Ni-base to pure Co-base superalloys have been assessed. Differential scanning calorimetry measurements and thermodynamic calculations match well and show that the γ ′ solvus temperature decreases with increasing Co-content. The γ / γ ′ lattice misfit is negative on the Ni- and positive on the Co-rich side. High Ni-contents decelerate the oxidation kinetics up to a factor of 15. The creep strength of the Ni-base alloy increases by an order of magnitude with additions of Co before it deteriorates strongly upon higher additions despite an increasing γ ′ volume fraction. Graphical abstract: